Calibration Method for Line-Structured Light Three-Dimensional Measurement Based on a Simple Target - Xuexing Li; Wenhui Zhang; Guanglei Song (Photonics, 2022)
Line-structured light three-dimensional (3D) measurement is apt for measuring the 3D profile of objects in complex industrial environments. The light-plane calibration, which is a crucial link, greatly affects the accuracy of measurement results. This paper proposes a novel calibration method for line-structured light 3D measurement based on a simple target, i.e., a single cylindrical target (SCT). First, the line-structured light intersects with the target to generate a light stripe. Meanwhile, the camera captures the calibration images, extracts the refined subpixel center points of the light stripe (RSCP) and detects the elliptic profiles of the two ends of the cylindrical target (EPCT). Second, two elliptical cones defined by the EPCT and the camera optical center are determined. Combining the two defined elliptical cones and the known radius of the SCT, we can uniquely solve the axis equation of the SCT. Finally, because the coordinates of RSCP in the camera coordinate system fulfill both the camera model and the cylindrical equation, these coordinates can be solved and used to obtain the optimal solution of the light-plane equation. The results of simulations and experiments verify that our proposed method has higher accuracy and effectiveness.